Percepcja audytywna, właściwości akustyczne oraz cechy dystrybucyjne sylab w języku polskim - Śledziński, Daniel (Investigationes Linguisticae, 2015)
<!–[if gte mso 9]> 72 <![endif]–> This paper presents experiments concerning properties of selected CV syllables. Acoustic speech signal related to particular syllables was analyzed using artificial neural networks. The goal of the analyses was to investigate whether realizations of particular syllables retain acoustic features distinctive of these syllables. Aditionally, a perception test aiming at identification of the same syllable set was carried out. In the test we analyzed to which degree it is possible to identify syllables isolated from the linguistic context. The paper discusses also results on distributional properties of syllables which indicate that such properties may play a significant role in speech perception. <!–[if gte mso 9]> 72 <![endif]–><span style="font-size: 12.0pt; font-family: 'Georgia','serif'; mso-fareast-font-family: 'ヒラギノ角ゴ Pro W3'; mso-bidi-font-family: 'Times New Roman'; color: black; mso-ansi-language: PL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Percepcja audytywna, właściwości akustyczne oraz cechy dystrybucyjne sylab w języku polskim<!–[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>